The Relationship Between Paraoxonase, Arylesterase, Lipoprotein(a) and Other Lipid Parameters in Patients with Complicated and Undeveloped Type II Diabetes Mellitus - Özdin, Mehmet; Gürsu, Mehmet Ferit (Balıkesir Üniversitesi, 2021)
Aim: Type II diabetes mellitus (type II DM) is very common today and is among the important causes of mortality. Our aim in this study is to determine the relationship between paraoxonase1 (PON1), arylesterase (ARE), lipoprotein (a) [Lp (a)] and other lipid parameters in patients with complicated and undeveloped type II DM.Material and Method: Serum PONl, ARE, Lp (a), apo A, apo B and other lipid parameters of 40 type II DM patients, 20 of whom did not develop complications, and 20 developed complications, who applied to Fırat University Hospital Endocrinology clinic were investigated. The control group consists of 40 healthy individuals without cardiovascular disease, diabetes or a disease affecting serum lipid level. Result: Serum PONl, ARE, total cholesterol, triglyceride, HDL-K, LDL-K, VLDL-K, Lp (a), apo A and apo B levels were significantly different in patients with type II DM complications compared to the healthy control group (p<0.05). Serum HDL-K, LDL-K, Lp (a) and Apo A levels were significantly different in patients without type II DM complications (p<0.05). However, serum PONl and ARE activities, total cholesterol, triglyceride, VLDL-K and apo B levels did not differ significantly from healthy control (p>0.05). Conclusion: PONl, ARE, total cholesterol, triglyceride, HDL-K, LDL-K, VLDL-K, Lp (a), apo A and apo B control of these parameters will affect the prevention of complications and the course of the disease positively.

Amaç: Tip II diabetes mellitus (tip II DM) günümüzde çok sık görülmekte olup önemli mortalite nedenleri arasındadır. Bu çalışmadaki amacımız komplikasyon gelişmiş ve gelişmemiş tip II DM hastalarında paraoksonaz1 (PON1), arilesteraz (ARE), lipoprotein(a) [Lp(a)] ve diğer lipit parametreleri arasındaki ilişkiyi belirlemektir.Gereç ve Yöntemler: Fırat Üniversitesi Hastanesi Endokrinoloji kliniğine başvuran 20 komplikasyon gelişmeyen, ve 20 komplikasyon gelişmiş olmak üzere 40 tip II DM hastasının serum PONl, ARE, Lp(a), apo A, apo B ve diğer lipid parametreleri araştırıldı. Kontrol grubu kardiyovasküler hastalığı, diyabeti veya serum lipid düzeyini etkileyen bir hastalığı olmayan sağlıklı 40 bireyden oluşmaktadır. Bulgular: Tip II DM komplikasyon gelişmiş olan hastalarda serum PONl, ARE, total kolesterol, trigliserid, HDL-K, LDL-K, VLDL-K, Lp(a), apo A ve apo B düzeyleri sağlıklı kontrol grubuna göre anlamlı farklılık bulundu (p<0.05). Tip II DM komplikasyon gelişmeyen hastalarında serum HDL-K, LDL-K, Lp(a) ve Apo A düzeyleri sağlıklı kontrol göre anlamlı olarak farklı idi (p<0.05). Ancak serum PONl ve ARE aktiviteleri, total kolesterol, trigliserid, VLDL-K ve apo B düzeyleri sağlıklı kontrol göre anlamlı farklılık gösterdiği saptanmadı (p>0.05). Sonuç: Tip II DM hastalarında PONl, ARE, total kolesterol, trigliserid, HDL-K, LDL-K, VLDL-K, Lp(a), apo A ve apo B bu parametrelerin kontrolünün yapılması komplikasyonların önlenmesini ve hastalığın seyrini olumlu yönde etkileyecektir.
Komplikasyon Gelişmiş ve Gelişmemiş Tip II Diabetes Mellitus Hastalarında Paraoksonaz, Arilesteraz, Lipoprotein(a) ve Diğer Lipit Parametreleri Arasındaki İlişki
Keywords: Clinical Sciences; Klinik Tıp Bilimleri